A Cross-Linguistic Research into Phonetic Iconicity - Lívia Körtvélyessy (Lexis: Journal in English Lexicology, 2011)
Phonetic iconicity in evaluative morphology is an integral part of sound symbolism in natural languages. Former research in this field has brought contradictory results. On the one hand, there is Universal #1926 (Plank and Filimonova’s Universals Archive, Konstanz) claiming universal marking of diminutives by front high vowels, and of augmentatives by high back vowels. Furthermore, there are papers extending the idea of phonetic iconicity to the front-back opposition of consonants. On the other hand, there are studies (Ultan [1978], Nieuwenhuis [1985], Gregová, Körtvélyesssy and Zimmermann [2009]) indicating that (a) this phenomenon is of areal rather than universal nature; (b) there are substantial differences between languages within individual genetic families, (c) front high vowels are typical of augmentatives rather than diminutives; diminutive affixes are acoustically realized by central vowels.The paper presents the results of cross-linguistic research into a balanced sample of 60 languages of the world. The focus is this time on the verification of the hypothesis in question by comparing languages of various genetic, geographical and morphological types. Special attention is paid to (a) checking the postulated front-back opposition in languages with both morphological diminutives and augmentatives, (b) the relevance of phonetic iconicity in terms of geographical, genetic, and morphological classifications of the sample languages; comparison of the data obtained with the results arrived at in the previous stages of our research which dealt with 35 European languages. The discussion is supported by numerous examples.